Hubungan Kualitas Hidup Dengan Risiko Depresi Pegawai Publik Universitas X Dimasa Pandemi COVID-19 - Shoma Rizkifani; Muhammad Akib Yuswar; Eka Kartika Untari; Nia Resseda (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
COVID-19 pandemic has had a significant negative impact on the sub-dimension of quality of life, a decrease in quality of life is also correlated with levels of depression. This study aimed to determine the relationship between quality of life and the risk of depression in X University public employees during the COVID-19 pandemic. This research is an analytic observational study and uses a cross-sectional analytic approach, the number of samples is 121 respondents who were selected using a purposive sampling technique. Data were obtained from filling out self-data, quality of life questionnaire (EQ-5D-5L), and depression questionnaire (PHQ-9). The analysis used in this research is a univariate analysis and bivariate analysis. Bivariate analysis using Spearman correlation test. The results showed that most respondents were male, aged 45 years. Respondents have a level of quality of life with a good quality of life category of as much as 57% and a poor quality of life level of as much as 43% and respondents have a level of depression with a mild depression category as much as 26.4%, a moderate depression level as much as 5.8% and a severe depression level as much as 2.5%. The relationship between quality of life and the risk of depression was found to be significant with a significance value of 0.000 with sufficient strength in the negative direction. This study concludes that there is a significant negative relationship between quality of life and the risk of depression in X University public employees during the COVID-19 pandemic.